2018
DOI: 10.1242/jeb.177451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water temperature on diel feeding, locomotion behaviour and digestive physiology in sea cucumber Apostichopus japonicus

Abstract: This study used controlled laboratory conditions to directly assess the role of water temperature in controlling diel feeding and locomotion behaviours, and digestive physiology, in the sea cucumber The results revealed that both the proportion of feeding individuals and ingestion rate were highest at 16°C. Regardless of water temperature, sea cucumbers appeared to be nocturnal and their peak feeding activity occurred at 00:00 h to 04:00 h. Tentacle insertion rate was not significantly correlated with water te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…There are two reasons for why the injection made at this time point: (1). Sea cucumbers are very sensitive to lights (Dong et al, 2010; Sun et al, 2018), and their physiological status and activities are totally adjusted to dark at 3 h after turning to dark. (2).…”
Section: Methodsmentioning
confidence: 99%
“…There are two reasons for why the injection made at this time point: (1). Sea cucumbers are very sensitive to lights (Dong et al, 2010; Sun et al, 2018), and their physiological status and activities are totally adjusted to dark at 3 h after turning to dark. (2).…”
Section: Methodsmentioning
confidence: 99%
“…It was generally accepted that the digestive enzyme activities of sea cucumber were affected by many factors such as food composition, culturing temperature, water salinity, intestinal microflora, and so on (Gao, Yang, Xu, Wang, & Liu, ; Sun et al, ; Yuan et al, ; Zhao et al, ). In this study, it were found that the activities of amylase, cellulase and alginase of the sea cucumber significantly increased when fed with fermented kelp residue, while protease activity had no significant increase.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies regarding effects of temperature or salinity stress on sea cucumbers have been extensively reported, primarily focusing on oxygen consumption, energy metabolism, molecular response, etc. (Bai et al, ; Dong et al, ; Kuhnhold et al, ; Meng et al, ; Ning et al, ; Sun et al, ). However, the more practically combined effects of temperature and salinity on A .…”
Section: Discussionmentioning
confidence: 99%
“…Temperature and salinity are considered as the main physiological factors affecting aquatic animals in ecological systems (Kinne, , ). Previous studies have demonstrated that temperature (Dong, Dong, Tian, Wang, & Zhang, ; Dong, Ji, Meng, Dong, & Sun, ; Kuhnhold et al, ; Ning et al, ; Sun et al, ) and salinity (Bai et al, ; Geng et al, ; Meng, Dong, Dong, Yu, & Zhou, ) are closely related to growth, behaviour, survival and physiological metabolism of sea cucumber A . japonicus .…”
Section: Introductionmentioning
confidence: 99%